Editorial: What is the Language of Science?New Consensus Statements in Spanish - Luis Fernando Aragón Vargas (Universidad de Costa Rica, 2023)
Reflections are presented about the publication of the first two consensus statements in Spanish. Publication of this type of information is key to promote evidence-based practice in human movement science professionals.